Ashṭādaśa śatakera Mughala saṃkaṭa o ādhunika itihāsa cintā - Bandyopādhyāẏa, Śekhara (Itihāsera bitarkita samasyā granthamālā, 1983)
On the causes of the fall of Mogul Empire in the 18th century, in the light of the contemporary sociopolitical and economic environment.